(untitled) (SciELO Preprints, 2021)
BACKGROUND: In March 2020, the World Health Organization (WHO) declared the COVID-19 outbreak a pandemic. In Brazil, the high rate of dissemination made it necessary to adopt restrictive measures nationwide with the discussion regarding the resumption of economic activities starting in April. In mid-December the country had 6,970,034 cases diagnosed and 182,799 deaths from COVID-19. OBJECTIVE: To analyze the content and characteristics of official documents, which guided the period of transition and resumption of economic activities in Brazil based on health indicators. METHODS: This is a documental research, carried out between May and July 2020, using official websites and publications from the state governments of the 27 federative units in Brazil as sources. In the study, only documents that used epidemiological and health indicators were included as determining criteria for decision making in relation to the easing, permanence or regression of social isolation measures adopted during the COVID-19 pandemic. FINDINGS: Plans, decrees and technical notes were identified for 18 Brazilian federal units. In most documents, the scientific team was made up exclusively of technicians (n = 10). The number of indicators found ranged from 2 to 11, being stratified into 5 categories: frequency and distribution of the disease; social and collective adherence; installed capacity or service profile; productive potential; and availability of supplies. MAIN CONCLUSIONS: Knowing governmental strategies, adopted in the easing of restrictive measures, in the face of the coronavirus (SARS-CoV-2) pandemic based on indicators and with the possibility of comparison between different federative units, provides subsidies for understanding the outcome of the disease by place of occurrence, allowing the construction of a panorama pathology in the country. The appropriation of the findings of this study by Brazil and other countries also serves as an instrument for reflection and planning of policies adopted during the COVID-19 pandemic.